Biocatalytic Process for Production of α-Glucosylglycerol Using Sucrose Phosphorylase - Christiane Luley-Goedl; Thornthan Sawangwan; Mario Mueller; Alexandra Schwarz; Bernd Nidetzky (Food Technology and Biotechnology, 2010)
Glycosylglycerols are powerful osmolytes, produced by various plants, algae and bacteria in adaptation to salt stress and drought. Among them, glucosylglycerol (2-O-α-D-glucopyranosyl-sn-glycerol; GG) has attracted special attention for its promising application as a moisturizing agent in cosmetics. A biocatalytic process for the synthesis of GG as industrial fine chemical is described in which sucrose phosphorylase (from Leuconostoc mesenteroides) catalyzes regioselective glucosylation of glycerol using sucrose as the donor substrate. The overall enzymatic conversion, therefore, is sucrose+glycerol→GG+D-fructose. Using a twofold molar excess of glycerol acceptor in highly concentrated substrate solution, GG yield was 90 % based on ≥250 g/L of converted sucrose. Enzymatic GG production was implemented on a multihundred kg-per-year manufacturing scale, and a commercial product for cosmetic applications is distributed on the market under the name Glycoin®. Technical features of the biotransformation that were decisive for a successful process development are elaborated. Stabilization of proteins is another interesting field of application for GG.